2020
DOI: 10.4315/jfp-19-594
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of Thermometer Use by Consumers When Preparing Ground Turkey Patties

Abstract: ABSTRACT The purpose of this study was to test the effectiveness of an intervention for consumer thermometer use by using a randomized experimental design and direct observation of meal preparation. The study was conducted in test kitchen facilities in two locations in North Carolina (one urban and one rural). Cameras recorded participants' actions at various locations throughout the kitchen and recorded the meal preparation from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Thermometer video intervention did not affect quantifiable cross-contamination. Although the video did significantly increase the likelihood of thermometer use in the intervention group (P , 0.001) (11), it did not affect the prevalence, concentration, or number of surfaces contaminated with MS2 (P . 0.05; Figs.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Thermometer video intervention did not affect quantifiable cross-contamination. Although the video did significantly increase the likelihood of thermometer use in the intervention group (P , 0.001) (11), it did not affect the prevalence, concentration, or number of surfaces contaminated with MS2 (P . 0.05; Figs.…”
Section: Discussionmentioning
confidence: 92%
“…Intended washing method affected the presence of MS2 on kitchen utensils. Observations from previous studies have suggested that people who rely on dishwashers to clean their kitchen utensils may be more likely to crosscontaminate those same utensils compared with individuals who rely on manual washing (11). For this reason, we systematically recorded the intended washing method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the proximate compositional analyses of the ground turkey breast (a 500-g composited portion from each of three trials; N = 1, n = 3), as conducted by a private testing laboratory according to methods approved and described by the Association of Official Analytical Chemists (AOAC, 2012), were as follows: 0.6 ± 0.46% fat, 72.3 ± 0.25% moisture, 25.7 ± 0.25% protein, pH 5.67 ± 0.24, and a w 0.990 ± 0.001. The meat was inoculated, formulated, shaped, cooked, and sampled using methods described in our previous studies (Duong et al, 2020;and Luchansky et al, 2013and Luchansky et al, , 2020. In brief, ground turkey (ca.…”
Section: Inoculation and Cooking Of Ground Turkeymentioning
confidence: 99%
“…For example, various studies tracking shopping, storage, or preparation in-home have shown that many consumers risk of foodborne illness from improper handling of food [ 15 , 16 , 17 , 18 , 19 ]. Even when preparing food at laboratory kitchen sites, consumers have shown that they often do not follow recommended practices [ 20 , 21 , 22 ], which can result in cross contamination. Previous studies have shown that consumers have misconceptions regarding proper food handling and refrigerator storage techniques including RTE foods [ 23 , 24 , 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%